Stress-Induced, p53-Mediated Tumor Growth Inhibition of Melanoma by Modulated Electrohyperthermia in Mouse Models without Major Immunogenic Effects - Besztercei, Balázs (Int J Mol Sci, 2019)
Modulated electrohyperthermia (mEHT), an innovative complementary technique of radio-, chemo-, and targeted oncotherapy modalities, can induce tumor apoptosis and contribute to a secondary immune-mediated cancer death. Here, we tested the efficiency of high-fever range (~42 °C) mEHT on B16F10 melanoma both in cell culture and allograft models. In vivo, mEHT treatment resulted in significant tumor size reduction when repeated three times, and induced major stress response as indicated by upregulated cytoplasmic and cell membrane hsp70 levels. Despite the increased PUMA and apoptosis-inducing factor 1, and moderate rise in activated-caspase-3, apoptosis was not significant. However, phospho-H2AX indicated DNA double-strand breaks, which upregulated p53 protein and its downstream cyclin-dependent kinase inhibitors p21(waf1) and p27(kip). Combined in vitro treatment with mEHT and the p53 activator nutlin-3a additively reduced cell viability compared to monotherapies. Though mEHT promoted the release of damage-associated molecular pattern (DAMP) damage signaling molecules hsp70, HMGB1 and ATP to potentiate the tumor immunogenicity of melanoma allografts, it reduced MHC-I and melan-A levels in tumor cells. This might explain why the number of cytotoxic T cells was moderately reduced, while the amount of natural killer (NK) cells was mainly unchanged and only macrophages increased significantly. Our results suggest that mEHT-treatment-related tumor growth control was primarily mediated by cell-stress-induced p53, which upregulated cyclin-dependent kinase inhibitors. The downregulated tumor antigen-presenting machinery may explain the reduced cytotoxic T-cell response despite increased DAMP signaling. Decreased tumor antigen and MHC-I levels suggest that natural killer (NK) cells and macrophages were the major contributors to tumor eradication.